Effect of diet on postprandial glycemic and insulin responses in healthy dogs - Vastolo, Alessandro; Gizzarelli, Manuela; Ruggiero, Alessio; Alterisio, Maria Chiara; Calabrò, Serena; Ferrara, Maria; Cutrignelli, Monica Isabella (Frontiers in Veterinary Science, 2023)
Dog owners have gradually changed their approach, paying more attention to the nutrition and health of their animals. Various pet-foods with different ingredients and nutritional characteristics are available on the market. The study aimed to evaluate the administration of three diets (two grain-free GF1, GF2, and one grain-based, CB) with different sources of carbohydrates that can influence the glycemic and insulin postprandial responses in healthy dogs. When dogs fed GF2 diet showed the highest level of albumin and mean insulin concentration (p<0.001). Furthermore, GF1 diet caused the smallest (p<0.001) glucose and insulin area under the curve (AUC) and the lowest (p<0.05) glucose Nadir. Otherwise, group GF1 showed the highest (p<0.01) insulin time to peak. The GF2 diet showed the highest level of albumin, while reported the lowest amount of fructosamine (p<0.05). When dogs fed diet GF2 resulted in the highest (p<0.001) level of insulin Zenit. The cereal-based (CB) diet reported the highest amount of fructosamine (p<0.05). When dogs fed CB diet had the highest levels of glucose and the highest (p<0.001) glucose and insulin mean concentration. Diet CB reported the lowest (p<0.001) insulin Nadir. Diets with different carbohydrate sources and chemical compositions could modulate the glycemic response in healthy dogs. Bearing in mind that glycaemic/insulin postprandial responses influence energy availability and that different dogs have specific lifestyles; it may be preferable to also consider this aspect when choosing a maintenance diet for animals.